In vivo increase in thrombin generation by four‐factor prothrombin complex concentrate in apixaban‐treated healthy volunteers. (21st September 2015) - Cheung, Y. W.; Barco, S.; Hutten, B. A.; Meijers, J. C. M.; Middeldorp, S.; Coppens, M.
Summary Background Four‐factor prothrombin complex concentrate (PCC) (Cofact; Sanquin Blood Supply) 50 IU kg−1 increased thrombin generation beyond baseline values in healthy, rivaroxaban‐treated subjects. Objective To assess whether infusion with doses of 37.5 IU kg−1 and 25 IU kg−1 PCC reverses the anticoagulant effect of high‐dose apixaban, another oral direct factor Xa inhibitor. Methods In a randomized, double‐blind, placebo‐controlled, crossover study, six healthy subjects received twice‐daily apixaban 10 mg for 3.5 days followed by a single bolus of 37.5 IU kg−1 PCC, 25 IU kg−1 PCC, or placebo. The primary outcome was the effect of PCC 15 min after infusion on thrombin generation (endogenous thrombin potential [ETP]); secondary outcomes were the immediate effect of PCC on prothrombin time (PT) and the effect of PCC as compared with placebo over a period of 24 h on ETP and PT. Results Fifteen minutes after infusion of 37.5 IU kg−1 and 25 IU kg−1 PCC, ETP increased from 41% ± 11% to 56% ± 23% (P = 0.06) and from 44% ± 12% to 51% ± 15% (P = 0.03), respectively. ETP significantly differed over time between 37.5 IU kg−1 PCC and placebo during 24 h after infusion (P < 0.01). Both PCC doses restored apixaban‐induced PT prolongation after 15 min (P < 0.01), and this was sustained over a period of 24 h. Conclusion Both 37.5 IU kg−1 PCC and 25 IU/kg PCC improved coagulation parameters in healthy subjects, suggesting partial reversal of the anticoagulant effect of apixaban. This implies that PCC might be considered in patients with apixaban‐associated bleeding. However, ETP was not immediately restored to pre‐apixaban levels, suggesting that these doses are too low to instantly and fully restore hemostasis at peak apixaban levels.